Mini review of metabolism in leukaemia: from complexity to the clinic - Rattigan, Kevin M. (Frontiers in Hematology, 2024)
The importance of metabolism to cancer has increasingly been recognised and this is particularly the case for leukaemia. This has opened the possibility of targeting dysregulated metabolism with the aim of increasing the effectiveness of current therapies, some of which are anti-metabolites. One key challenge to be addressed is avoiding negative side effects due to shared metabolic dependencies between leukaemic and normal cells. This Mini Review will discuss how our understanding of wideranging effects of metabolism is continuing to evolve thanks to recent discoveries, as well as how metabolism can both directly and indirectly affect leukaemia cell functions. This includes introducing how metabolism is compartmentalised at levels ranging from organelle to whole body as well as how the metabolome can modify other 'Omes.' This Mini Review also places a focus on the overlay in metabolic demands of normal haematopoietic and immune cells. Finally, how therapies targeting metabolic processes have already delivered success, as well as the promise of new therapies targeting metabolism that are currently being investigated in clinical trials, will also be discussed.